Individual effects of l‐arginine or l‐lysine on stability of pork or chicken emulsion sausages with partial replacement of porcine backfat by soybean oil. (10th October 2021) - Wang, Yan; Hu, Yue; Li, Yakai; Li, Rui; Pan, Dongmei; Fang, Hongmei; Ye, Yongkang; Xu, Baocai; Zhou, Cunliu
Summary: The individual effects of l ‐arginine or l ‐lysine on the physical (cooking loss (CL), total expressible fluid (TEF) and expressible fat (EFAT)) and chemical (thiobarbituric acid‐reactive substances (TBARS), and carbonyl and total sulphhydryl (T‐SH) content) stability of pork or chicken emulsion sausage with partial replacement of porcine backfat by soybean oil were determined. l ‐arginine or l ‐lysine increased pH but decreased CL, TEF and EFAT. Confocal laser scanning microscopy revealed that supplementation with l ‐arginine or l ‐lysine caused more regular and uniform oil droplets, for enhanced physical stability of pork or chicken sausage. Subjected to the same treatments, chicken sausage displayed higher physical stability than pork sausage. Overall, chicken sausages treated with l ‐arginine or l ‐lysine had lower TBARS and carbonyl content but higher T‐SH content than the corresponding control during storage; for pork sausages, l ‐arginine or l ‐lysine treatment generally resulted in higher TBARS throughout storage, lower carbonyl content during the initial 14 days and higher T‐SH content on days 7 and 14 but lower T‐SH content on days 1 and 21. Generally, l ‐arginine/l ‐lysine effectively increased the chemical stability of chicken sausage but decreased the chemical stability of pork sausage. Abstract : Mechanism for l‐arginine or l‐lysine affects stability of pork or chicken emulsion sausages.